An Analysis upon Contribution of CRM Success Factors for Banking Performance Enhancement: Developments and Implementation: Exploring the Factors for Successful CRM Implementation in the Retail Banking Sector (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Customer Relationship Management is emerging as a new phenomenon however; relationship oriented marketing practices date back to the Pre-Industrial Era. The current study explores the CRM best practices currently being followed in Indian Retail Banking Sector. It provides an integrated view to Indian Banks and to every employee in the organization, that they should be empathetic towards their customers and should treat them fairly. Customers have lot more choices available today than ever before. The only way to attract and retain customers is create, manage and develop relations with customers, thereby resulting in maximized total customer lifetime value.Conceptually, customer relationship management (CRM) has been widely embraced by businesses. In practice, however, examples of success contrast with anecdotes where the diffusion of CRM into organizations continues to be a slow process and/or where CRM implementation outcomes have fallen short of expectations.Successful implementation of CRM initiatives depends on a number of factors such as information quality, system quality, service quality, top management support, and technological readiness were empirically tested. Moreover, major indicators (measures) of successful implementation of CRM initiatives such as increasing customer retention rate, increasing customer acquisition rate, deepening relationship with customers, and improving customer satisfaction are also empirically tested. Building on the results of a survey of the CRM-implementation-related experiences of 18 Jordan based banks with 154 self-administered questionnaire participants in this study, the authors identify factors associated with successful CRM implementation and identify indicators of successful or effective implementation and highlight the implications of the study findings for future research.